Developing Cultural Intelligence and Empathy Through Diversified Mentoring Relationships. (June 2018) - Young, Cheri A.; Haffejee, Badiah; Corsun, David L.
Given increasing globalization and the foreign-born workforce characterizing many organizations around the world, managers are increasingly called on to effectively manage a culturally diverse workforce. One way to increase the cultural intelligence and empathy of managers was proposed by Ragins, who indicated that mentors in diversified mentoring relationships (DMRs) may become more culturally intelligent and empathic as a result of exposure to the situations and challenges faced by their lower power protégés. To test this proposition regarding the efficacy of DMRs, a quasi-experimental design was employed using an experiential training intervention involving DMRs between primarily White, affluent student mentors and newly resettled refugees to the United States. Grounded in the theoretical foundations of contact theory and DMRs, our findings suggest that DMRs of even limited duration may be influential in increasing cultural intelligence and empathy.